Triceps brachii muscle architecture, upper-body rate of force development, and bench press maximum strength of strong and weak trained participants - Nikolaos Zaras; Angeliki-Nikoletta Stasinaki; Polyxeni Spiliopoulou; Thomas Mpampoulis; Gerasimos Terzis (Termedia Publishing House, 2022)
Purpose The study aim was: (a) to investigate the relationship between triceps brachii muscle architecture and upperbody isometric rate of force development (RFD), isometric peak force (IPF), and maximum strength (one-repetition maximum, 1-RM) in bench press and (b) to explore whether triceps brachii architecture might determine RFD, IPF, and 1-RM strength in stronger and weaker participants. Methods The study involved 21 males (age: 22.6 ± 4.7 years, weight: 76.6 ± 10.2 kg, height: 1.79 ± 0.07 m) with 3.4 ± 2.1 years of experience in resistance training. They were divided into a strong and weak group depending on their relative 1-RM strength in bench press. Measurements included triceps brachii muscle architecture, upper-body isometric RFD, IPF, and 1-RM strength in bench press. Results Moderate to large correlations were found for triceps brachii thickness and fascicle angle with upper-body RFD ( r : 0.379-0.627), IPF ( r : 0.582 and 0.564, respectively), and 1-RM strength in bench press ( r : 0.530 and 0.412, respectively). Maximum strength in bench press was largely correlated with IPF ( r = 0.816); moderate to very large correlations were observed with RFD ( r : 0.499-0.725). The strong group presented significantly higher 1-RM relative strength, RFD, and IPF ( p < 0.05) than the weak group, but no significant between-group difference was found for triceps brachii architecture ( p > 0.05). Conclusions Triceps brachii architecture correlates with 1-RM strength, upper-body RFD, and IPF in trained participants. However, triceps brachii architecture may not distinguish upper-body strength and RFD between stronger and weaker male participants.